AQUATIC BIORESOURCES OF ASHTAMUDI LAKE, RAMSAR SITE, KERALA - Vimal Raj, R.V; Binushma Raju; Soumya, W; Shibu A; Lekshmi, S; Shibu Vardhanan; Sruthi, S and Tresa Radhakrishnan (Journal of Aquatic Biology & Fisheries, 2014)
Ninety one species of f ishes and shellf ishes belonging to 39 families were collected from the Ashtamudi Lake, Ramsar site No. 1204, that comprised 68 species of finfishes, 5 species of crabs, 9 species of prawns and 9 species molluscs. The majority of them were marine forms. The once very rich f ishery resources of the Lake has considerably declined over the years. Pollution, sand mining reclamation, loss of mangrove habitat and destructive fishing methods are the main reasons for loss of f ishery diversity in the Lake.